2015
DOI: 10.2217/fmb.15.129
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Prophylaxis: Why, What and How?

Abstract: 41st Annual Meeting of the European Society for Blood and Marrow Transplantation (EBMT 2015), Istanbul, Turkey, 22-25 March 2015 The European Society for Blood and Marrow Transplantation (EBMT) is the leading scientific society for professionals involved in hematopoietic stem-cell transplantation (HSCT) and represents 563 transplant centers from 57 countries within and outside Europe. Each year, the EBMT Annual Meeting brings together over 4,500 scientists, physicians, nurses, biologists, technicians and patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Despite the introduction of newer antifungal agents, 24 candidaemia (the most common form of invasive candidiasis) is associated with unacceptably high mortality rates 25 . To reduce the burden of candidaemia and Candida‐ related mortality in high‐risk patients (especially AML or HSCT patients), haematology and/or HSCT units in many hospitals are increasingly adopting systemic antifungal prophylaxis 4 . A comparison of two large SEIFEM studies conducted in two 5‐year periods (1999‐2003 and 2011‐2015) showed a significant decrease in the overall incidence of candidaemia in patients who received chemotherapy for haematology malignancies (170/9258 [1.8%] vs 135/16 529 [0.8%]; P < .001) 10 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite the introduction of newer antifungal agents, 24 candidaemia (the most common form of invasive candidiasis) is associated with unacceptably high mortality rates 25 . To reduce the burden of candidaemia and Candida‐ related mortality in high‐risk patients (especially AML or HSCT patients), haematology and/or HSCT units in many hospitals are increasingly adopting systemic antifungal prophylaxis 4 . A comparison of two large SEIFEM studies conducted in two 5‐year periods (1999‐2003 and 2011‐2015) showed a significant decrease in the overall incidence of candidaemia in patients who received chemotherapy for haematology malignancies (170/9258 [1.8%] vs 135/16 529 [0.8%]; P < .001) 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Since 2005, the European Conference in Infections in Leukaemia (ECIL) designed evidence‐based clinical guidelines to improve the management of patients at high risk of infectious complications due to the treatment of leukaemia or following HSCT 4 . The latest ECIL guidelines included the use of mould‐active antifungal prophylaxis to prevent IFD 4 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations